1920
DOI: 10.5962/bhl.title.3974
|View full text |Cite
|
Sign up to set email alerts
|

The nature of animal light

Abstract: Co-enzyme, 104, 130 Co-luciferase, 107 ff Color of animal light, 41 ff, 157 ff Concentration and luminiscence, 145 ff

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

1925
1925
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…I n the second edition of Buchner's book (1930), however, the matter is left undecided. Harvey and Hall (1929) demonstrated that the development and functioning of the adult light organ in Photuris pennsylvanica is unaffected by ablation of the larval organs. They concluded, therefore, that bactrria are not concerned with luminescence.…”
Section: Annals New York Academy Of Sciencesmentioning
confidence: 99%
“…I n the second edition of Buchner's book (1930), however, the matter is left undecided. Harvey and Hall (1929) demonstrated that the development and functioning of the adult light organ in Photuris pennsylvanica is unaffected by ablation of the larval organs. They concluded, therefore, that bactrria are not concerned with luminescence.…”
Section: Annals New York Academy Of Sciencesmentioning
confidence: 99%
“…Each cubic centimeter of eggs corresponded to approximately 5 X 106 eggs. The cytochrome oxidase values per cubic centimeter of eggs were converted to a wet weight and a dry weight basis using an egg density of 1.08 (10) and an egg solid content of 18 per cent (11). To carry out the preparation, the eggs, either unfertilized or at 30 minutes after fertilization at 20°C., were packed tightly by centrifuging at 2000 times gravity for l0 minutes.…”
Section: Experim'ental Methodsmentioning
confidence: 99%
“…Judean forensic process differed from Roman in three principal areas (Falk: 98-110;Harvey;Derrett 1971: 178-91).…”
mentioning
confidence: 98%